تقرير عن ندوة علمية بعنوان: علم معاني القرآن الكريم" أوضاع ومقاصد" بالمملكة المغربية - يوسف فاوزي (Tadabbur Journal)
تقرير عن ندوة علمية بعنوان: علم معاني القرآن الكريم" أوضاع ومقاصد" بالمملكة المغربية